Introduction to Wald (1949) Statistical Decision Functions - Weiss, L. (Breakthroughs in Statistics, 1991)
Abraham Wald was born on October 31, 1902 in Cluj, one of the main cities of Transylvania, which at the time belonged to Hungary. The official language was Hungarian, but the population was mixed, containing substantial numbers of Romanian, German, and Jewish inhabitants, as well as Hungarians. As a result, much of the population spoke more than one language, and the Jewish families used Yiddish as well as Hungarian. Wald’s family would not allow their children to attend school on Saturday, the Jewish sabbath, and as a result, Wald was educated at home until he attended the local university, where the language of instruction was Hungarian. After graduating from the local university, he entered the University of Vienna in 1927 and received his Ph.D. in mathematics in 1931. His first research interest was in geometry, and he published 21 papers in that area between 1931 and 1937. Austria was in turmoil during much of this period as a result of Nazi agitation, and it was impossible for Wald, as a Jewish noncitizen, to obtain any academic appointment. He supported himself by tutoring a prominent Viennese banker and economist, Karl Schlesinger, in mathematics. As a result of this, Wald became interested in economics and econometrics, and published several papers and a monograph on these subjects. His first exposure to statistical theory was a natural result of his work on econometrics. Because of his publications in econometrics, Wald was invited to become a Fellow of the Cowles Commission and arrived in the United States in the summer of 1938. This invitation from the Cowles Commission saved Wald’s life, for almost the whole of his family in Europe perished during the Holocaust. In the fall of 1938, Wald became a fellow of the Carnegie Corporation and started to study statistics at Columbia University with Harold Hotelling. Wald stayed at Columbia as a Fellow of the Carnegie Corporation until 1941, lecturing during the academic year 1939-40. In 1941, he joined the Columbia faculty and remained a member of that faculty for the rest of his life. During the war years, he was also a member of the Statistics Research Group at Columbia, doing research related to the war effort. In late 1950, Wald was giving a series of lectures in India at the invitation of the Indian government. On December 13, 1950, he and his wife were killed when their airplane crashed.